Inggris-Sasak: Perubahan Fonem /f/ dan /v/ dalam Bahasa Inggris oleh Pedagang Asong di Sekitar Sirkuit Mandalika Lombokrcuit Lombok - Nurhandini, Hilmi; Sulistyowati, Sulistyowati (Humanis; Vol 28 No 2 (2024), 2024)
This research is a phonological study that focuses on changes in the phoneme /f/ and /v/ in the use of English by hawkers around Mandalika Circuit, Lombok. This study aims to classify the forms and factors of phoneme changes /f/ and /v/ in the use of English by hawkers around Mandalika Circuit. The method of this research is descriptive qualitative. The data is the utterances containing phonemes /f/ and /v/ from 25 hawkers. The intralingual identity method is used to analyze the form of phoneme change, and Weinreich’s theory (1979) is used to analyze the factors of phoneme change. The result shows that the phonemes /f/ and /v/ changed because the Sasak language did not have the phonemes /f/ and /v/, so there was a process of simplifying English into the Sasak language and creating local English variation. The local English variation is created due to the bilingualism of hawkers, low loyalty to English, and getting into a habit of Sasak language.